Correlation between GDF-15 gene polymorphism and the formation of collateral circulation in acute ST-elevation myocardial infarction - Chen,Xiao-ping (2017)
Summary Objective: To explore the correlation between growth differentiation factor 15 (GDF-15) -3148C/G polymorphism and the formation of collateral circulation in acute ST-elevation myocardial infarction (STEMI) in Han population of Taiyuan area. Method: The present study included 92 STEMI patients and 56 normal controls based on coronary angiography; STEMI group was divided into collateral group and non-collateral group according to Rentrop's grading method. Polymerase chain reaction (PCR) and DNA sequencing methods were used to detect and analyze the GDF-15 -3148C/G polymorphism in all participants. Results: There was significant difference in GDF-15 -3148C/G CC and GC distribution between STEMI group and control group (p=0.009); the allele frequencies between these two groups were also significant different (p=0.016); and the risk genotype for STEMI was CC with increased OR=2.660. For STEMI group, GDF-15 -3148C/G CC and GC distribution was also significantly different between patients with and without collateral (p=0.048), and CC genotype significantly promote the formation of collateral circulation. However, there were no significant differences in allele frequencies between these two subgroups of STEMI. Conclusion: There was correlation between GDF-15-3148C/G polymorphism and the formation of collateral circulation in patients with acute STEMI.